The role of modeling in visual learners’ awareness of the basics of perspective in art education - Hussein Rashak Khudhair ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
The aim of the current research is to reveal the role of modeling in visual learners’ awareness of the basics of perspective in the subject of art education. Therefore, the research population consisted of middle school students (third year of middle school), whose number reached (650) students. The researcher chose (20) students as a sample for his research using this method. Randomization, adopting the one-group experimental approach, and after applying the experiment and collecting data through the research tool (visual perception test), the researcher concluded that modeling has a role in learners’ visual perception after this was proven statistically by the appearance of a significant difference between the pre-test and the post-test for one group, and this is what made the researcher recommend Using modeling to develop learners’ visual awareness of the basics of perspective .